CONSIDERATIONS ON COMMON PRACTICAL APPLICATIONS OF NORMAL DISTRIBUTION - CĂTĂLIN ILIE MITRAN (Annals of the University of Petrosani: Economics)
In the case of a large number of practical considerations, such as those related to the distribution coefficient of the population’s intelligence, the ratio between motivation and performance, but also the distribution of the average of an exam in the case of a large number of competitors, it can be seen that these tend to follow similar results to those given by the normal distribution. For these reasons, the study of these phenomena can be described using the normal distribution.